Ixekizumab in the treatment of psoriatic arthritis - Yu. L. Korsakova; T. V. Korotaeva (Научно-практическая ревматология, 2024)
Psoriatic arthritis (PsA) is characterized by a combination of musculoskeletal and extra-articular manifestations, such as peripheral arthritis, axial disease, dactylitis, enthesitis, uveitis, inflammatory bowel disease, psoriasis (Ps). Currently, great progress has been made in the study of the pathogenesis of PsA and pharmacotherapy of this disease. The article presents data on the efficacy and safety of the IL-17 inhibitor ixekizumab (IXE). IXE demonstrates high therapeutic efficacy against all clinical manifestations of PsA in most patients, regardless of concomitant methotrexate intake and previous intake of biological disease-modifying antirheumatic drugs, the presence of cardiometabolic comorbidity. This drug delays the progression of destructive processes in the joints. IXE is indicated for patients with Ps of problematic localization: palmar-plantar, anogenital, scalp and nails.